2019
DOI: 10.3892/mmr.2019.10040
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 stimulates Mc3T3‑E1 osteoblast differentiation and mineralization through autophagy induction

Abstract: Vitamin K2 likely exerts its protective effects during osteoporosis by promoting osteoblast differentiation and mineralization. However, the precise mechanism remains to be fully elucidated. Autophagy maintains cell homeostasis by breaking down and eliminating damaged proteins and organelles. Increasing evidence in recent years has implicated autophagy in the development of osteoporosis. The aim of the present study was to verify whether vitamin K2 (VK2) can induce autophagy during the differentiation and mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 36 publications
3
47
0
2
Order By: Relevance
“…VK2 was found to reinstate the expression of LC3-II, PINK1 and Parkin, thereby restoring osteoblast autophagy and mitophagy. The positive effects of VK2 on autophagy is consistent with previous report (Li et al, 2019). To further explore the beneficial roles of VK2, 3-MA, a potent autophagy inhibitor, was used in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…VK2 was found to reinstate the expression of LC3-II, PINK1 and Parkin, thereby restoring osteoblast autophagy and mitophagy. The positive effects of VK2 on autophagy is consistent with previous report (Li et al, 2019). To further explore the beneficial roles of VK2, 3-MA, a potent autophagy inhibitor, was used in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Various reports have further demonstrated that dietary VK2 supplementation is associated with improved bone formation status, reduced risk of GIOP, and lowered the prevalence of osteoporotic fracture (Sasaki et al, 2005;Iwamoto et al, 2010;Weng et al, 2019). Recent findings further indicate that the pro-osteoblastic effects of VK2 is mediated by enhanced autophagic activities (Li et al, 2019), but whether mitophagy is also associated with VK2's beneficial effects in osteogenesis remains to be determined. In this study, we aim to investigate the potential beneficial effects of VK2 against the deleterious effects of GC (Dexamethasone; Dex) on osteoblasts particularly in terms of mitophagy and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that CSE exposure significantly decreased hOB cell viability compared to the control and MBE groups; pre-incubation with MBE could significantly prevent the decreased cell viability caused by CSE. AP is an important marker for osteoblast activity during early osteoblast differentiation (Li et al, 2019[ 27 ]). As shown in Figure 6D (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well reported that dysregulation of autophagy is capable of disturbing bone development and results in bone disorders (Kim & Lee, 2014). Accumulating evidence has suggested that autophagy can stimulate differentiation and mineralization in MC3T3‐E1 cells (Kim et al, 2016; Li, Zhang, Liu, Liu, & Liang, 2019). Furthermore, AMPK‐/mTOR‐mediated autophagy has been reported to exhibit a marked effect on bone protection (Cheng et al, 2019; Kneissel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%